Effective design of optical code-division multiple access network using random diagonal codes - Hilal Adnan, Fadhil, Dr.; Syed Alwee Aljunid, Syed Junid, Prof. Dr.; R. Badlishah, Ahmad, Assoc. Prof. Dr. (Institute of Electrical and Electronics Engineers (IEEE), 2012)
Link to publisher's homepage at http://www.ieee.org/